EFFECT OF CONE THERAPY ON URINARY STRESS INCONTINENCE - Malekzadegan, A; S Khanjari; Yadavar-Nikravesh, M; Hosseini, F; Neisani, L (Iran University of Medical Sciences, 2002)
Background: Stress incontinence is the most common types of urinary incontinence in women and the second factor for permanent incontinence in old women, which effects on their health and quality of life. Basic treatment for this problem is pelvic floor exercises. Usage of vaginal cones is an effective intervention for prevention and treatment of urinary stress incontinence. Objective: To determine the effect of cone therapy on urinary stress incontinence. Design: This was a before- after clinical trial without control group. In which subject, used vaginal cones (20 to 70 gram) twice a day each time for 15 minutes during 3 months except on menstrual period. Data were evaluated by assessing the pelvic floor strength, through perineometery, and the number and amount of leakage during stress, through self reporting before and after cone therapy. Sample: 53 patients were selected consecutively. Result: The findings indicated a significant decrease in frequencies and amount of urine leakage after cone therapy (P< 0.0001), and 45.3 percent of subjects cured completely. Conclusion: The results showed that cone therapy is an effective method for the treatment of urinary stress incontinence. Therefore, it is recommended that cone therapy be used as a supportive treatment for this problem.